Exploring conditions for just lithium mining in South America: The case of the EU responsible sourcing strategy - Murguia, Diego Ignacio (2024)
To advance its climate neutrality and electromobility goals, the European Union (EU) depends on a reliable supply of lithium. The "lithium triangle", comprising Chile, Argentina, and Bolivia, contains 53% of the world's lithium resources and supplies 85% of the EU's lithium imports. In 2023, the EU and Latin America launched a new cooperation agenda under which the EU signed Memorandums of Understanding (MoUs) with Chile and Argentina aimed at jointly developing sustainable value chains for critical raw materials. That same year, the EU adopted the European Batteries Regulation (EBR), which mandates due diligence to address social and environmental risks in the mining of battery minerals. The EBR and MoUs form the foundation of the EU's responsible sourcing strategy for lithium from South America. This study, using the energy justice framework and results from a Delphi survey, investigates whether the EBR and MoUs align with the conditions for a just lithium battery value chain for the lithium triangle. Our findings indicate that the EU-South America agenda reflects cumulative learning by addressing mutual interests, such as local industrialization. However, the current EU responsible sourcing approach overlooks critical local-level justice considerations —distributive, procedural, and recognition justice— that are highly relevant to the lithium triangle. We argue that for the EU to ensure a just lithium supply from South America, additional issues must be prioritized, including the equitable participation of local communities in the economic benefits of lithium mining, institutional strengthening, and the proper implementation of free, prior, and informed consultation with Indigenous peoples.